FORECAST OF GEOLOGICAL PROFILE BASED ON DETAILED PROCESSING OF SEISMIC MATERIALS IN THE SOFTWARE-ALGORITHMIC COMPLEX «GEOSEIF» - Alexander I. Kochegurov; Viktor P. Ivanchenkov; Oleg V. Orlov (Известия Томского политехнического университета: Инжиниринг георесурсов, 2019)
Relevance. It is well known that the main objectives of forecasting a geological section are to determine the material composition of sedimentation, to select the productive strata and to assess their petroleum potential. These goals are achieved, among other things, on the basis of detailed processing and interpretation of seismic data with reference to the results of well logging. In modern software and algorithmic complexes for processing and interpreting seismic information, the amplitude and energy characteristics of the reflected waves are mainly used as diagnostic signs for prediction of a geological profile. Phase frequency characteristics for this purpose of the forecast are practically not used. All this leads to the fact that when solving the problems of forecasting a geological profile, the percentage of erroneous decisions is quite large and the allocation of false anomalies of dynamic and kinematic parameters of reflections occurs quite often. The aim of the research is to obtain a forecast of the geological section using new informative parameters extracted from the instantaneous phase spectra of the reflected seismic waves on the basis of the detailed processing of seismic materials in the software and algorithmic complex «Geoseif». Methods and means of research: digital signal processing and space-time fields, discrete Fourier transform, mathematical modeling methods, computational experiment. Results. The composition of the software and algorithmic complex «Geoseif» and the list of tasks solved on it are considered in detail. It is shown that the general approach to solving the problems on the «Geoseif» complex is associated with the formation of the selected route in accordance with the accepted processing graph from the available source data to the desired results. The paper presents the structure of the detailed processing of seismic materials during the implementation of phase-frequency deconvolution algorithms for predicting a geological section. As a result of application of the considered methodology, a phase-time analysis of the territory of the Dvurechensko-Karandashovskaya zone was conducted and a zoning map was drawn for the selected types of geological section. At the same time, the identified correlation links between the values ​​of the phase response and the zonal and local lithological and tectonic inhomogeneities of the section are interpolated and extrapolated into the interwell space.